2017
DOI: 10.1080/0194262x.2017.1349715
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Library Services at Engineering News Record’s Top 500 Design Firms: Ten Years Later

Abstract: This paper reports on the findings of a national survey of the library services available at Engineering News Record's Top 500 Designs Firms. In mid-October 2002, a survey was mailed to all 500 firms. The survey was in two parts. One part was to be completed by a principal in the firm. The second part was to be completed by the degreed librarian (holding a Masters in Library Science or its equivalent) if the firm employed one. The findings indicated that 74.4 percent of responding design firms do not employ a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In a survey of employers, Harding and McPherson (2010) found that 58% of respondents "agree that there is a need for engineers who possess the fundamentals of standards development and the knowledge to find and apply standards prior to employment." Likewise, both Jeffryes and Lafferty (2012) and Napp (2017) found that engineers (co-op students and professionals, respectively) reported needing to use standards in their on-the-job experiences more frequently than any other resource type.…”
Section: Introductionmentioning
confidence: 97%
“…In a survey of employers, Harding and McPherson (2010) found that 58% of respondents "agree that there is a need for engineers who possess the fundamentals of standards development and the knowledge to find and apply standards prior to employment." Likewise, both Jeffryes and Lafferty (2012) and Napp (2017) found that engineers (co-op students and professionals, respectively) reported needing to use standards in their on-the-job experiences more frequently than any other resource type.…”
Section: Introductionmentioning
confidence: 97%
“…A current trend in STEM educational research involves transforming qualitative outcomes into quantitative data for statistical analysis and generalization (Borrego, Douglas, & Amelink, 2009;Teddlie & Tashakkori, 2003). There are many examples of this in the field of engineering education literature (Borrego et al, 2009;Compton, 1995;Dabbagh & Menasce, 2006;Napp, 2004;Vanderburg & Khan, 1994). Researchers apply a framework of categorization to qualitative data such as open-ended focus group questions and then quantify the results based on repeatability of responses.…”
Section: Methodsmentioning
confidence: 99%
“…The study reviewed more than 400 literature items published over a 40 year span and found that 40 to 66% of working time was spent related to processing, communicating, and disseminating information. In another study, Napp [15,16] surveyed engineers at the top 500 design firms, per Engineering News Record, in 2004 and again in 2014, which found that of information sources most often needed by engineers, 92.4% of respondents indicated standards. Conversely, engineering faculty from a 2011 survey still view journal articles as the most important information source for their students.…”
Section: Literature Reviewmentioning
confidence: 99%